Effect of proliferating cell nuclear antigen ubiquitination and chromatin structure on the dynamic properties of the Y-family DNA polymerases. - Sabbioneda, S; Gourdin, A; Green, C; Zotter, A; Giglia-Mari, G; Houtsmuller, A; Vermeulen, W; Lehmann, A (2008)
Y-family DNA polymerases carry out translesion synthesis past damaged DNA. DNA polymerases (pol) eta and iota are usually uniformly distributed through the nucleus but accumulate in replication foci during S phase. DNA-damaging treatments result in an increase in S phase cells containing polymerase foci. Using photobleaching techniques, we show that poleta is highly mobile in human fibroblasts. Even when localized in replication foci, it is only transiently immobilized. Although ubiquitination of proliferating cell nuclear antigen (PCNA) is not required for the localization of poleta in foci, it results in an increased residence time in foci. poliota is even more mobile than poleta, both when uniformly distributed and when localized in foci. Kinetic modeling suggests that both poleta and poliota diffuse through the cell but that they are transiently immobilized for approximately 150 ms, with a larger proportion of poleta than poliota immobilized at any time. Treatment of cells with DRAQ5, which results in temporary opening of the chromatin structure, causes a dramatic immobilization of poleta but not poliota. Our data are consistent with a model in which the polymerases are transiently probing the DNA/chromatin. When DNA is exposed at replication forks, the polymerase residence times increase, and this is further facilitated by the ubiquitination of PCNA.